Farewell to Mushtaqur Rahman: An AMSS Pioneer (American Journal of Islam and Society, 1999)
Professor Mushtaqur Rahman, a renowned Muslim geographer, who wasborn on July 1,1933 in Agra (India), died of cardiac arrest at Des Moines,Iowa (USA), on November 5, 1999. He had heart problems for severalyears that had slowed down his academic and social service activities butnever deterred him from performing them.In 1947, he migrated to Pakistan, a country he loved dearly and lived toserve throughout his life. Still, his contributions went beyond it in a numberof ways. Having done his B.A. (1953) and M.A. (1955) from theUniversity of Karachi, he taught at Islamiah College, Karachi, and SindhUniversity, Hyderabad for a few years. He earned his Ph.D. degree inCultural Geography, from Louisiana State University in 1960, and didpostdoctoral research at the University of Geisen, Germany in 1966-67. Heserved in the Department of Geography, University of Karachi, Pakistanfrom 1963 to 1969. He was appointed Professor of Geography in theDepartment of Anthropology, Iowa State University (ISU), Ames, Iowa.He served ISU till his retirement in May 1998.Dr.. Rahman’s contribution to the field of Cultural Geography of SouthAsia has been recognized worldwide. In Professor Rahman was combinedan activist and quiet researcher. He was a founding member of the OldStudents’ Association of Karachi University (OSAKU), which he served invarious capacities. Besides carrying out advisory duties for the MuslimStudents Association at ISU, he organized for its students and faculty manystudy tours of Pakistan and brought a number of Pakistani scholars to IowaState.His main scholarly contributions are through his very long, sincere, dedicatedservice to the Association of Muslim Social Scientists (AMSS) andthrough his many worthy publications in the field of political and culturalgeography. Not only did he serve AMSS as its vice president with one ofits founders, Dr. AbdulHamid AbuSulayman, but he was also elected its ...